Comparison of electrophoretic protein profiles of Campylobacter jejuni subsp. jejuni isolated from different animal species - Scarcelli,Eliana (2001)
Electrophoretic protein profiles of Campylobacter jejuni subsp. jejuni strains isolated from feces of seven animal species, including man, were compared. Fourteen strains (two from each species) plus two human strains and the reference one, were ruptured by ultrasound and their total soluble proteins were analyzed by SDS-PAGE technique in a 12% polyacrylamide gel with computerized densitometric reading by the molecular analyst software. All the strains had bands in common that correspond to 45 and 66 Kda molecular weight. The disagreement corresponded to a 97 to 200 Kda molecular weight region. From the 17 strains, 13 (76.5%), were classified as biotype I, three (17.6%) as biotype II and one (5.8%) as biotype III. Since protein extracts were obtained from cells grown under identical conditions, and thus, able to express the same phenotype, this disagreement region could be related to different genotypes or serotypes.